Novos paradigmas produtivos da notícia: usos da infografia interativa na prática webjornalística - Lima, Patrícia Medeiros de (2016)
The focus of this paper is centered on the analysis of how Interactive Infographics has been used for reporting and reconfiguring the productive dynamics of the news. Thereunto, six infographics of the website Jornal Folha de São Paulo were analyzed as a webjornalística and infographic construction. With technological development new forms of communication have emerged through the Internet Culture and transformations occurred mainly in the field of journalism, directly affecting its productive practice. The main objective of the dissertation focuses on analyzing the use of interactive infographic language in the production processes of journalistic web news. We start from an exploratory research was used to observe and analysis of infographics chosen as corpus. This study enabled the discovery of the phenomenon of infonews, which are made news with interactive infographics resources and that are framed in that concern the productive processes of journalism.